Understanding Social Status through Social Deixis and Politeness Strategy in German Series Maxton Hall: The World Between Us - Cattleya Ismi Arafah (UIN Salatiga, 2026)
Using Brown and Levinson's (1987) approach, this study examines how politeness and social deixis are used in the German television series Maxton Hall: The World Between Us. The study uses a qualitative descriptive methodology, collecting, classifying, and analyzing data according to the model developed by Miles and Huberman. The analysis finds 196 social deixis, including 35 politeness strategies and relational and absolute forms. Relational social deixis, which mainly expresses intimacy between speakers, seems to occur far more frequently than absolute deixis. The characters' attempts to maintain their dignity and negotiate hierarchical relationships in the affluent setting of Maxton Hall are also evident in the prevalence of Negative Politeness and Off-record strategies. The results imply that politeness strategies and social deixis serve as linguistic instruments for communicating familiarity, controlling social distance, and resolving power dynamics. All things considered, this study shows how Maxton Hall language reflects larger societal trends in German communication, where deixis and politeness are used to strike a balance between authority and intimacy in intricate social structures.